Electromyography of the Multifidus Muscle in Horses Trotting During Therapeutic Exercises - Ursini, Tena; Shaw, Karen; Levine, David; Richards, Jim; Adair, Henry Steve (Frontiers in Veterinary Science, 2022)
Thoracolumbar pain has been identified in both human and equine patients. Rehabilitation and conditioning programs have focused specifically on improving trunk and abdominal muscle function [1-5]. Equine exercise programs routinely incorporate ground poles and training devices for the similar goals of increasing spinal and core stability and strength [6-8]. The multifidus muscle has been an area of focus due to atrophy associated with disease [9]. To date, there have been no reports on the activity of the multifidus muscle in horses in relation to therapeutic exercises. Our objectives were to use electromyography to determine the average work performed and peak muscle activity of the multifidus in horses trotting, trotting over ground poles, trotting while wearing a resistance band-based training device and trotting while wearing the training device over ground poles. We hypothesized that ground poles and the training device would each increase average work performed and peak multifidus muscle activity. Right and left cranial thoracic locations showed significant increased muscle work and peak activation when horses were trotted over ground poles versus without. The peak activation was significantly greater in horses trotting over poles in both lumbar regions, but there was no significant change in peak activation in either location due to the training device. When the influence of the training device was investigated without ground poles, left caudal thoracic muscle work and peak activity, and right lumbar muscle work were significantly lower when using the training device, as compared to without. When the training device was combined with trotting over ground poles, both left and right caudal thoracic regions showed significantly lower muscle work and peak activity when the device was used. There was no significant difference between with and without the device in either left or right lumbar muscle work. In conclusion, implementing ground poles can be an effective strategy to increase the activation of the multifidus muscle, however, caution should be taken when incorporating the resistance band training device as muscle work and peak activation were significantly reduced in most locations. Further study should be performed with the training device to determine its effects on epaxial musculature.